Pengaruh Suku Bunga dan Nilai Tukar Terhadap Harga Saham Dengan Profitabilitas Sebagai Variabel Moderasi Pada Perusahaan Pertambangan 2021-2023 - Nuraini, Assyifa Putri; Hijriah, Amanah; Kurniawan, Rudy (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The purpose of this study was to determine how the effect of interest rates and exchange rates on stock prices with profitability represented by RoE (Return on Equity) as a moderating variable in mining companies. Quantitative method is the method used in this research. The object of research is mining companies for the period 2021-2023 and obtained a sample using purposive sampling method of 38 companies. From the results of data processing using SPSS 25 in the partial test (t test) found that the interest rate and exchange rate variables had no effect on stock prices. In the Moderated Regression Analysis (MRA) test, it was found that RoE weakened the relationship between interest rates and stock prices. Meanwhile, RoE strengthens the relationship between exchange rates and stock prices. Suggestions for future researchers are expected to use or add more relevant economic factors to test their influence on stock prices and increase the research period.
Keywords: Interest Rate; Exchange Rate; Stock Price; ROE